2019
DOI: 10.1007/978-3-030-17127-8_22
|View full text |Cite
|
Sign up to set email alerts
|

A Sound and Complete Logic for Algebraic Effects

Abstract: This work investigates three notions of program equivalence for a higher-order functional language with recursion and general algebraic effects, in which programs are written in continuation-passing style. Our main contribution is the following: we define a logic whose formulas express program properties and show that, under certain conditions which we identify, the induced program equivalence coincides with a contextual equivalence. Moreover, we show that this logical equivalence also coincides with an applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…There is a very large body of methods for proving program equivalence, and in particular contextual equivalence, in higher-order languages with state, probabilities, and effects; see e.g. [Benton et al 2014;Bizjak and Birkedal 2015;Crubillé and Lago 2015;Jung et al 2015;Matache and Staton 2019;Pitts and Stark 1998]. Many of these methods have been applied to reason about security and privacy, using the natural view of adversaries as contexts.…”
Section: Related Workmentioning
confidence: 99%
“…There is a very large body of methods for proving program equivalence, and in particular contextual equivalence, in higher-order languages with state, probabilities, and effects; see e.g. [Benton et al 2014;Bizjak and Birkedal 2015;Crubillé and Lago 2015;Jung et al 2015;Matache and Staton 2019;Pitts and Stark 1998]. Many of these methods have been applied to reason about security and privacy, using the natural view of adversaries as contexts.…”
Section: Related Workmentioning
confidence: 99%
“…This is a desirable property, since any two programs related by a congruence are contextually equivalent. Moreover, in [17,18] it is shown that for a continuation-passing style language, such a program equivalence coincides with contextual equivalence.…”
Section: Simulations and Equalitymentioning
confidence: 99%
“…We capture such observations with a collection of predicate liftings [27,18]. These consist of a set of tokens denoting each possible observation, and for each token a device that lifts a predicate on return values to a predicate on coinductive trees over these values.…”
Section: Introductionmentioning
confidence: 99%
“…Plotkin and Pretnar [2008] propose a generic logic for algebraic effects that encompasses Moggi's computational λ-calculus, evaluation logic, and Hennesy-Milner logic, but does not extend to Hoare-style reasoning for state. Simpson and Voorneveld [2018] and Matache and Staton [2019] explore logics for algebraic effects by specifying the effectful behaviour of algebraic operations using a collection of effectspecific modalities instead of equations. Their modalities are closely related to how we derive effect observations θ : M → W Pure and thus program specifications from M-algebras on P in §4.4, as intuitively the conditions they impose on their modalities ensure that these can be collectively treated as an M-algebra on P. In recent work concurrent to ours, Voorneveld [2019] studies a logic based on quantitative modalities by considering truth objects richer than P, including S → P for stateful and [0, 1] for probabilistic computation.…”
Section: Related Workmentioning
confidence: 99%